The China-Pakistan economic corridor (CPEC): Considering contemporary Pakistan through old-fashioned economics and historical case studies - McCartney, M (Lahore School of Economics, 2018)
As part of the massive One Belt One Road (OBOR) project or ‘New Silk Road’ the governments of China and Pakistan have announced that a significant ‘corridor’ will be constructed in Pakistan. This paper looks in detail at the $46 billion China-Pakistan Economic Corridor (CPEC) package of transport, energy and manufacturing projects and asks how we can analyse the impact of a transformative expansion of infrastructure. This paper draws lessons from various old-fashioned economics including Rostow, Hirschman and others and the historical case studies of transformative infrastructure expansion in the nineteenth century United States, Mexico, Germany and India to explore the conditions under which CPEC could promote sustainable long-run economic growth in Pakistan.